2018
DOI: 10.1111/bph.14430
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin modifies growth, proliferation and apoptosis of human colon organoids: a protease‐activated receptor 1‐ and protease‐activated receptor 4‐dependent mechanism

Abstract: Background and PurposeThrombin is massively released upon tissue damage associated with bleeding or chronic inflammation. The effects of this thrombin on tissue regrowth and repair has been scarcely addressed and only in cancer cell lines. Hence, the purpose of the present study was to determine thrombin's pharmacological effects on human intestinal epithelium growth, proliferation and apoptosis, using three‐dimensional cultures of human colon organoids.Experimental ApproachCrypts were isolated from human colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Organoids were plated in 96-wells opaque plates after 6 or 9 days of culture. CellTiter-Glo R 3D reagent (Promega, France) was added to each well (volume 1:1), and incubated for 30-min at room temperature (Sébert et al, 2018). Triplicate measures were performed for each condition.…”
Section: Metabolic Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Organoids were plated in 96-wells opaque plates after 6 or 9 days of culture. CellTiter-Glo R 3D reagent (Promega, France) was added to each well (volume 1:1), and incubated for 30-min at room temperature (Sébert et al, 2018). Triplicate measures were performed for each condition.…”
Section: Metabolic Activity Assaymentioning
confidence: 99%
“…In the presence of appropriate growth factors, intestinal stem cells present in the isolated crypts proliferate and enter into differentiation processes, recreating a complex epithelium, which contains all cell types that compose the intestinal epithelium (paneth cells, enteroendocrine cells, goblet cells, enterocytes, tuft cells, etc.). The epithelium generated by three-dimension cultures of isolated crypts closes on itself, forming a sphere, in which epithelial cells are orientated with their apical side toward the lumen (Sébert et al, 2018). While a number of studies have employed culture organoids from intestinal crypts (Sugimoto et al, 2018;Yip et al, 2018;Ramesh et al, 2019), only very few studies have investigated the possibility to culture organoids from IBD patient-isolated intestinal crypts (Dotti et al, 2017;Noben et al, 2017;Howell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PAR 1 activation triggered Akt activation and colonoid growth [7]. Furthermore, we have shown that PAR 1 is implicated in the maturation and apoptotic behavior of primary colonoids treated by thrombin [8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in human colon organoid cultures, we reported that thrombin significantly reduces the size of budding structures, metabolic activity and proliferation, while increasing apoptosis. In the same study, we reported that both PAR1 and PAR4 antagonists inhibited apoptosis regardless of thrombin doses (91).…”
Section: Pars and Intestinal Homeostasismentioning
confidence: 84%